Nanomaterials : Toxicity, Human Health and Environment - Clichici, Simona; Filip, Adriana; do Nascimento, Gustavo M.; Clichici, Simona; Filip, Adriana; do Nascimento, Gustavo M. (IntechOpen, 2020)
In the last decade, nanomaterials have become a double-edged sword. On one hand, nanomaterials have proven their limitless potential not only for technological applications, but also for medical ones. On the other hand, the increasing use of these nanomaterials has raised concerns regarding their safety for environmental and human health, due to their potential toxicity. The toxic effects of nanomaterials depend on their type, surface geometry, diameter, length and function. This book intends to provide a comprehensive evidence-based overview of nanomaterial toxicity, from their synthesis and characterization, environmental impact, tests to assess their toxicity in vitro and in vivo, ways to modulate their impact on living organisms, to their beneficial use in biomedical applications.
English
Keywords: Materials science; Materials science